2018
DOI: 10.31234/osf.io/sxdah
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the Reproducibility of Experimental Philosophy

Abstract: For scientific theories grounded in empirical data, replicability is a core principle, for at least two reasons. First, unless we accept to have scientific theories rest on the authority of a small number of researchers, empirical studies should be replicable, in the sense that its methods and procedure should be detailed enough for someone else to conduct the same study. Second, for empirical results to provide a solid foundation for scientific theorizing, they should also be replicable, in the sense that mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…Despite high statistical power, the RPP observed a replication success rate of only 36% (when success was defined as a statistically significant result in the expected direction) and found that the replication effects were, on average, only half as strong as the original effects (Open Science Collaboration, 2015). Similar projects in economics and experimental philosophy have also obtained replicability estimates considerably lower than would be expected in the absence of published false positives, although results have varied somewhat across projects (Camerer et al, 2016;Cova et al, 2018). These findings reinforce concerns about the replicability of behavioral science and suggest that replicability may vary both between and within disciplines.…”
Section: The Replicability Of Behavioral Sciencementioning
confidence: 67%
See 2 more Smart Citations
“…Despite high statistical power, the RPP observed a replication success rate of only 36% (when success was defined as a statistically significant result in the expected direction) and found that the replication effects were, on average, only half as strong as the original effects (Open Science Collaboration, 2015). Similar projects in economics and experimental philosophy have also obtained replicability estimates considerably lower than would be expected in the absence of published false positives, although results have varied somewhat across projects (Camerer et al, 2016;Cova et al, 2018). These findings reinforce concerns about the replicability of behavioral science and suggest that replicability may vary both between and within disciplines.…”
Section: The Replicability Of Behavioral Sciencementioning
confidence: 67%
“…These findings reinforce concerns about the replicability of behavioral science and suggest that replicability may vary both between and within disciplines. For example, replicability appears to be higher for original studies that (a) examined main effects rather than interactions, (b) reported intuitive rather than surprising results, and (c) obtained a greater effect size, sample size, and strength of evidence (Camerer et al, 2016;Cova et al, 2018;Open Science Collaboration, 2015).…”
Section: The Replicability Of Behavioral Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…It would be concerning, then, if they turned out to be due to some idiosyncratic feature of Jim and his poetic ambitions. To address this issue, and in light of ongoing concerns about replicability in psychology and experimental philosophy (Earp and Trafimow 2015;Cova et al 2018;LeBel et al 2018), we decided to conduct a preregistered replication and extension study, in which we presented participants (between subjects) with four structurally similar vignettes-in addition to the one about Jim-describing other characters with a wide range of personal attributes and goals, but all with the shared feature of experiencing moral improvement versus deterioration as a result of starting or stopping the use of a drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may not be so simple. Recent work in psychology and experimental philosophy (see Knobe 2016;Knobe and Nichols 2008;Knobe et al 2012;Cova et al 2018) suggests that intuitions about changed identity are shaped not just by the fact of some change in demeanor after a transformative event (cf. Paul 2014), but rather by the particular kind of change that occurs.…”
Section: Introductionmentioning
confidence: 99%